Cardiac Safety Implications of hNav1.5 Blockade and a Framework for Pre-Clinical Evaluation - Erdemli, Gul; Kim, Albert M.; Ju, Haisong; Springer, Clayton; Penland, Robert C.; Hoffmann, Peter K. (Frontiers in Pharmacology, 2012)
The human cardiac sodium channel (hNav1.5, encoded by the SCN5A gene) is critical for action potential generation and propagation in the heart. Drug-induced sodium channel inhibition decreases the rate of cardiomyocyte depolarization and consequently conduction velocity and can have serious implications for cardiac safety. Genetic mutations in hNav1.5 have also been linked to a number of cardiac diseases. Therefore, off-target hNav1.5 inhibition may be considered a risk marker for a drug candidate. Given the potential safety implications for patients and the costs of late stage drug development, detection and mitigation of hNav1.5 liabilities early in drug discovery and development becomes important. In this review, we describe a preclinical strategy to identify hNav1.5 liabilities that incorporates in vitro, in vivo, and in silico techniques and the application of this information in the integrated risk assessment at different stages of drug discovery and development.